Virtual supply chain configuration : modeling and decision making - You, Xiao (2008)
This research proposes a virtual supply chain (VSC) framework for fulfilling individual customized orders in cooperation with worldwide partners through the support of advanced information and communication technologies. The rational of a VSC manifests itself through the configuration of legacy supply chain networks, in which a large number of varieties and their interdependency regarding product families, process platforms and logistics networks are synthesized coherently. VSC configuration entails the instantiation of a generic supply chain network into various specific supply chain variants in accordance with diverse customer requirements. Systematic and rigorous modeling methodologies are investigated in order to provide support to VSC implementation. A series of formalisms are established to articulate the VSC from an architectural perspective, involving data and information structures, variety configuration, and coordination across different functional areas. A domain-based framework is developed to reveal the coordination issues among product, process and supply chain design. A nested modular approach is developed to model the integration of hierarchical decisions within a VSC. To model the configuration mechanisms within a VSC, the colored Petri net technique is applied, through which dynamic decisions with respect to tradeoffs of various supply chain configuration structures are analyzed consistently.